Using photovoice to explore students’ emotions of learning to write: "There is something about writing" - Sari, Dini Rosita; Sultan, Sultan (JEES (Journal of English Educators Society), 2022)
The present study aimed to scrutinize how employing photovoice in writing class helped uncover novice writers’ emotions of learning to write. Eight secondary school students voluntarily participated in the two-session writing class. Accompanying the photovoice, the participants were also asked to write a reflective journal for additional data collection. Results indicate that these novice writers, though experienced confusion and encountered various problems, persisted in completing the writing assignment due to their intrinsic motivation. This suggests that teachers should incorporate in their teachings explanation of the importance of enhancing one’s writing competence to grow students’ motivation and interests in writing. HIGHLIGHTS : The participants of the present study found it challenging to generate ideas and revise their writing composition. Despite the struggle, secondary school students developed positive attitudes toward writing class. A good understanding of the importance of writing skill affected students’ determination to finish the writing tasks.